Integration of Biomechanics and Kinesiology in Improving Athlete Performance: Physiological and Biomechanical Perspectives - Andi Atssam Mappanyukki (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyze the integrative role between biomechanics and kinesiology in improving athletic performance from a physiological and biomechanical perspective. The study was conducted using a literature review method of scientific articles from the PubMed, ScienceDirect, BMC, SpringerLink, BMJ, and Google Scholar databases for the period 2020–2026. The results of the review show that the integration of these two disciplines contributes significantly to improving movement efficiency, explosive strength, and injury prevention. Biomechanics plays a role in analyzing force, joint moments, and muscle-tendon stiffness, while kinesiology explains motor control, movement coordination, and physiological adaptation to training loads. The reviewed studies confirm that exercises such as plyometrics and high loads increase tendon stiffness and energy transfer efficiency, while the use of wearable sensors enables real-time biomechanical monitoring to support coaching decisions. This integration also needs to consider biological factors such as gender, fitness level, and tissue condition in the design of training programs. Overall, the research results confirm that the biomechanics-kinesiology approach can create a more scientific, personalized, and adaptive training model, thereby supporting optimal athlete performance and reducing the risk of injury.